Determinant of Success English Reading Skills Among University Students: Remedial and Challenge Strategies: Faktor Penentu Keberhasilan Kemampuan Membaca Bahasa Inggris di Kalangan Mahasiswa: Strategi Remedial dan Tantangan - Singgih Prastawa (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
Reading comprehension skill is important requirement that must be possessed by college students in learning English. To support college students reading skill development, the role of lecturer and learning materials are crucial. This research aims to find empirical evidence the effect of learning process, college students activities, university facilities, and lecturer activities on English reading skills. This study applied quantitative method with causally associative approach. College students majoring of Management, Faculty of Economics, Universitas Slamet Riyadi Surakarta were being populations in this study. The research sample consisted of 110 college students and was selected through the use of purposive sampling. Partial Least Squares-Structural Equation Modeling (PLS-SEM) is used in the data analysis with SmartPLS. The result of this study indicate that learning process, university facilities and lecturer activities have significant effect on English reading skills in Faculty of Economics, Universitas Slamet Riyadi Surakarta. On the other hand, college students activities had no effect on English reading skills. The implication of this research is lecturer to be more creative in the use of technological media in learning that can make college students enjoy learning more. This research also provides valuable insights for educational institutions aiming to sustain and improve university quality by focusing on learning process and university facilities as key drivers of success.